Relationship Between Thiopurine S-Methyltransferase Genotype/Phenotype and 6-Thioguanine Nucleotide Levels in 316 Patients With Inflammatory Bowel Disease on 6-Thioguanine. Issue 5 (October 2021) - Bayoumy, Ahmed B.; Mulder, Chris J. J.; Loganayagam, Aathavan; Sanderson, Jeremy D.; Anderson, Simon; Boekema, Paul J.; Derijks, Luc J. J.; Ansari, Azhar R.
Abstract : Background: In inflammatory bowel disease (IBD), conventional thiopurine users cease treatment in 60% of cases within 5 years, mostly because of adverse events or nonresponse. In this study, the authors aimed to investigate the role of 6-thioguanine nucleotide (TGN) measurements, geno/phenotyping of thiopurine S-methyltransferase (TPMT), and their mutual relationship with TG therapy in IBD. Methods: An international retrospective, multicenter cohort study was performed at 4 centers in the Netherlands (Máxima Medical Centre) and the United Kingdom (Guy's and St. Thomas' Hospital, Queen Elizabeth Hospital, and East Surrey Hospital). Results: Overall, 526 6-TGN measurements were performed in 316 patients with IBD. The median daily dosage of TG was 20 mg/d (range 10–40 mg/d), and the median duration of TG use was 21.1 months (SD, 28.0). In total, 129 patients (40.8%) had a known TPMT status. In the variant-type and wild-type TPMT genotype metabolism groups, median 6-TGN values were 1126 [interquartile range (IQR) 948–1562] and 467.5 pmol/8 × 10E8 red blood cells (RBCs) (IQR 334–593). A significant difference was observed between the 2 groups ( P = 0.0001, t test). For TPMT phenotypes, in the slow, fast, and normal metabolism groups, the median 6-TGN values were 772.0 (IQR 459–1724), 296.0 (IQR 200–705), and 774.5 pmol/8 × 10E8 RBCs (IQR 500.5–981.5), with a significant difference observed between groups ( P < 0.001, analysis of variance). Conclusions: Our findings indicated that TPMT measurements at TG initiation can be useful but are not necessary for daily practice. TPMT genotypes and phenotypes are both associated with significant differences in 6-TGN levels between metabolic groups. However, the advantage of TG remains that RBC 6-TGN measurements are not crucial to monitor treatments in patients with IBD because these measurements did not correlate with laboratory result abnormalities. This presents as a major advantage in countries where patients cannot access these diagnostic tests.